PENEGAKAN HUKUM PERLINDUNGAN KONSUMEN SEBAGAI UPAYA PENINGKATAN MUTU PRODUKSI NASIONAL - Ali Mansyur; Irsan Rahman (Jurnal Pembaharuan Hukum, 2015)
As the Consumer Protection Law Enforcement Effort for Quality Improvement National Production outlines that globalization opens free market requires businesses to compete on a competitive basis from the galloping pace of international business competition. Opportunities entry of goods importedfrom abroad should be able to be supported by regulations to safeguard the rights of consumers and businesses nationwide are required to produce a quality prodak capable of fulfilling the rights of consumers and be able to compete competitively in the global market. The research method using normative juridical approach with The data collection methods focus on literature study materials secondary law. research shows that the production quality standardization aims to improve consumerprotection and to realize smooth trade and a healthy business climate, embody the fulfillment of the rights of consumers, and improve the quality of prodak grade; The next responsibility of businesses in ensuring the quality of the production is to provide the fulfillment of the rights of consumers, the conception of the activities prohibited to businesses in the form of regulations to not produce harmful products and are not qualified, and quality standardization efforts of national production; whereasconsumer protection law enforcement efforts in improving the quality of national production is through the efforts of standardizing the quality of production, the preventive consumer protection and dispute settlement, prosecution and sanctioning both on aspects of criminal, civil and administrative.